A Descriptive Study of Patient Safety Culture at Inche Abdoel Moeis Regional Hospital, Samarinda, Indonesia - Fierda Eka Pratiwi; Ratno Adrianto; Riyan Ningsih (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Patient safety culture is a key pillar in improving the quality of health services. In 2025, the Indonesian Ministry of Health adapted the Hospital Survey on Patient Safety Culture (HSOPSC) version 2.0 as a national instrument to measure hospital staff perceptions of patient safety culture. Objective : This study aimed to describe the patient safety culture based on the 2025 Ministry of Health’s Patient Safety Culture Survey Instrument at Inche Abdoel Moeis Regional Hospital, Samarinda. Research Methods/ Implementation Methods : A descriptive quantitative study with a cross-sectional approach was conducted using secondary data from the 2025 patient safety culture survey. The population included all healthcare workers and non-medical staff (n=259). Data were analyzed descriptively by calculating the average score of each dimension of patient safety culture. Results : The overall mean score was 3.66 (73.2%), categorized as good. The highest dimensions were general perception of safety (4.30), teamwork and collaboration (4.14), and organizational learning (4.08). The lowest were incident reporting (2.03), communication openness (2.40), and non- punitive response to errors (2.62). Conclusion/Lesson Learned : The patient safety culture at Inche Abdoel Moeis Regional Hospital was in the good category, although improvements are needed in incident reporting and non-punitive response aspects. Strengthening leadership commitment and implementing a safe, anonymous reporting system are essential to enhance the overall patient safety culture.